2012
DOI: 10.4314/njp.v39i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Childhood malignancies in University of Abuja Teaching Hospital Gwagwalada, Abuja, Nigeria.

Abstract: Abstract:Background: Mortality from malignancies in children remains high. Creating awareness of the disease and advocacy for funding of a cancer research center are pertinent. Objective: To determine the incidence and outcome of children with cancers at the University of Abuja Teaching Hospital, Gwagwaglada, Abuja-FCT, Nigeria Method: This was a 5 year prospective study of all diagnosed cancer patients admitted into the paediatric ward. The type of cancer, method of diagnosis, clinical staging and outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 8 publications
4
12
0
Order By: Relevance
“…4,5,6 The male preponderance observed in this study was comparable with previous reports in various parts of Nigeria, as well as in other resource-limited countries. 4,6,[13][14][15][16] Cultural and economic factors may account for the difference, as males usually benefit from more medical attention than females in these countries.…”
Section: Cancers and Mortalitysupporting
confidence: 81%
See 4 more Smart Citations
“…4,5,6 The male preponderance observed in this study was comparable with previous reports in various parts of Nigeria, as well as in other resource-limited countries. 4,6,[13][14][15][16] Cultural and economic factors may account for the difference, as males usually benefit from more medical attention than females in these countries.…”
Section: Cancers and Mortalitysupporting
confidence: 81%
“…4,5,6 The male preponderance observed in this study was comparable with previous reports in various parts of Nigeria, as well as in other resource-limited countries. 4,6,[13][14][15][16] Cultural and economic factors may account for the difference, as males usually benefit from more medical attention than females in these countries. 15 While studies in India, 4 Côte D'Ivoire 13 and western parts of Nigeria 16 found that children in the age bracket 5-9 years were most affected, under-fives children represented 55% of this study population.…”
Section: Cancers and Mortalitysupporting
confidence: 81%
See 3 more Smart Citations